A rare site of metastasis in lung cancer: Silent or loquacious? (Indian Journal of Case Reports, 2020)
Lung cancer is the most common cause of cancer-related deaths worldwide. Most of the lung cancer patients present at an advanced or metastatic stage (84%). Common sites of lung cancer metastasis are the liver, bone, brain, and adrenals. In our index case, we describe a rare site of metastasis in a 59-year-old gentleman that presented to us with cough and easy fatigability. On examination, he was pale and had crepitation’s in the left infrascapular region. The chest radiograph revealed a right hilar mass, which was confirmed on computed tomography. Bronchoscopy-guided biopsy revealed squamous cell lung cancer. Among significant baseline investigations, his hemoglobin was low (6.2 g/dl) with an elevated leukocyte and platelet count. Serum iron profile revealed a picture suggestive of anemia of chronic disease. Bone marrow examination was done, which revealed the presence of bone marrow metastasis with squamous cells. A diagnosis of Stage IVB squamous cell lung cancer with bone marrow metastasis was made and the patient was started on chemotherapy (carboplatin and paclitaxel). After the fourth cycle of chemotherapy, it was seen that the overall tumor was showing partial remission, and hemoglobin had also increased which was suggestive of bone marrow recovery. This demonstrates that bone marrow metastasis, though rare, needs not be silent overall.